Specific Features of the Subjective Picture of Life as Predictors of Readiness for Innovations of Future Law Enforcement Officers - A. M. Bolshakova (Law and Safety)
The objective of the research was to study the peculiarities of the subjective picture of life as personal predictors of the readiness of future law enforcement officers for innovations.